Increasing Resistance to Globalization: The Role of Trade in Tasks - Hartmut Egger; Christian Fischer (Center for Economic Studies and ifo Institute (CESifo), 2019)
Based on empirical evidence from cross-country survey data, we argue that the surge of trade in tasks over the last decades can explain increasing resistance to globalization in industrialized countries. In a traditional trade model of a small open economy, we demonstrate that public education provides protection against losses from trade in goods and services if trade increases the relative price of skill-intensive goods. Furthermore, increasing public schooling expenditure may help securing support for trade reform by a majority of voters. However, if education provides task-specific skills and trade in tasks makes some of these skills obsolete in the open economy, raising public schooling expenditure is of limited help to secure support for trade reform by a majority of voters, even if the reform is welfare-improving. Therefore, our analysis indicates that, in contrast to past episodes of globalization, public education does not shield workers from losses from trade in tasks and that drastic changes of the education system are needed in order to counter the increase of protectionist sentiments. To preserve majority support for trade reform, policy makers should adjust public education to provide broader, less-specialized skills. Although broader skills are less productive in a closed economy, acquiring them pays off as they increase the likelihood that a proposal for welfare-improving trade reform can be successful in a referendum.
Keywords: F11; F50; D72; I28; 330; resistance to globalization; trade in tasks; public education; majority voting